ANALISIS PENATAAN PERMUKIMAN KUMUH RENCANA KAWASAN 1 KOTA BANJARMASIN KUIN UTARA - ALALAK SELATAN - ALALAK TENGAH - ALALAK UTARA - Dwi Kurniasih; Ira Mentayani; Lilis Hartati; Zainal Abidin (EnviroScienteae, 2019)
The purpose of this research is to identify factors inhibiting the implementation of the arrangement of the slum area plan for Banjarmasin City. The method used in this study uses purposive sampling data collection techniques, namely secondary and primary (Questionnaire, interview, observation/observation) in the city of Banjarmasin. The method of data analysis with the help of SPSS 25 is to find out the Data Validation and Reliability Tests for the inhibiting factors in the arrangement of slums, the inhibiting index of the inhibiting factors in the structuring of slums, and the partial F test to find out the significant levels of the factors inhibiting the implementation of slums. The results of the research that have been carried out that obtained 20 implementation factors and 8 factors inhibiting the implementation of the arrangement of slums are low community income, lack of community involvement in decision making, documents that are not of good quality, non-functioning KPP (Development Maintenance Group), the quality of community self-help groups still low, the difficulty of changing people's behavior.